Oral health status, related behaviours and perceived stress in xerostomia, Sicca and Sjögren's syndromes patients - a cross-sectional study - Indre Stankeviciene; Lina Stangvaltaite-Mouhat; Jolanta Aleksejuniene; Diana Mieliauskaite; Ieva Talijuniene; Irena Butrimiene; Ruta Bendinskaite; Alina Puriene (BMC, 2024)
Abstract Background Mouth dryness increases the risk of some oral health-related conditions. Furthermore, it is unclear if patients with dry mouth engage in appropriate oral health-related behaviours. The study examined oral health, related behaviours, and perceived stress in dry-mouth patients and compared them to matched controls without mouth dryness. Methods Information about 182 dry-mouth patients and 302 age- and sex-matched subjects was retrieved. Three dry mouth groups: xerostomia, Sicca syndrome and Sjögren's syndrome, were formed based on patient self-reported and objectively assessed symptoms. The World Health Organization's Oral Health for Adults and Perceived Stress Scale (PSS-10) questionnaires inquired about sociodemographic characteristics, oral health-related behaviours, and self-perceived stress. Clinical oral health assessments included: caries experience measured as total numbers of decayed (DS), missing (MS), filled surfaces (FS), number of remaining teeth, erosive tooth wear and extent of periodontal pocketing. Data were analyzed using bivariate and multivariable tests. Results The dry-mouth participants had higher mean (SD) DMFS scores than their matched controls: xerostomia patients vs. controls: 74.6 (34.4) and 66.3 (35.4), Sicca syndrome patients vs. controls: 88.3 (34.0) and 70.1 (33.9), and Sjögren's syndrome patients vs. controls: 95.7 (31.5) and 74 (33.2). In comparison to controls, individuals with Sicca and patients with Sjögren's syndromes had lower mean (SD) number of remaining teeth, 15.9 (10.1) vs. 21.7 (8.4) and 13.8 (10.0) vs. 20.1 (9.2), and a lower mean (SD) extent of periodontal pocketing, 20.7 (28.6) vs. 41.1 (31.0), and 21.2 (24.1) vs. 34.8 (34.2), respectively. Xerostomia, Sicca syndrome and Sjögren's syndrome patients had higher odds of using fluoridated toothpaste; OR 1.8 (95%CI 1.1-2.9), OR 5.6 (95%CI 1.7-18.3) and OR 6.9 (95%CI 2.2-21.3), respectively. Participants with Sjögren's syndrome had lower odds of the last dental visit being within the last year; OR 0.2 (95%CI 0.1-0.8). Conclusions Dry-mouth patients had higher caries experience and fewer teeth than comparison groups but a lower extent of periodontal pocketing. Even though more participants with dry mouth used fluoridated toothpastes, their oral health-related behaviours were not optimal.